Matrine promotes mitochondrial biosynthesis and reduces oxidative stress in experimental optic neuritis - Song, Yifan; Wang, Mengru; Zhao, Suyan; Tian, Yanjie; Zhang, Chun (Frontiers in Pharmacology, 2022)
Optic neuritis (ON), characterized by inflammation of the optic nerve and apoptosis of retinal ganglion cells (RGCs), is one of the leading causes of blindness in patients. Given that, as an energy-intensive cell, RGC is vulnerable to mitochondrial dysfunction, improving mitochondrial function and reducing oxidative stress could protect these cells. Matrine (MAT), an alkaloid derived from Sophora flavescens, has been shown to regulate immunity and protect neurons in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis and ON. However, the protective mechanism of MAT on RGCs is largely unknown. In this study we show that MAT treatment significantly reduced the degree of inflammatory infiltration and demyelination of the optic nerve and increased the survival rate of RGCs. The expression of Sirtuin 1 (SIRT1), a member of an evolutionarily conserved gene family (sirtuins), was upregulated, as well as its downstream molecules Nrf2 and PGC-1α. The percentage of TOMM20-positive cells was also increased remarkably in RGCs after MAT treatment. Thus, our results indicate that MAT protects RGCs from apoptosis, at least in part, by activating SIRT1 to regulate PGC-1α and Nrf2, which, together, promote mitochondrial biosynthesis and reduce oxidative stress of RGCs.